Surah Al-Kahf and The Core of Relativity: How the Quran Foretold Spacetime Curvature, Gravity Wells and Wormholes - Mudassir, Mohd (Journal of Quranic Sciences and Research, 2025)
This research investigates the advanced scientific concepts of space-time curvature, wormholes, and time dilation as fundamental natural principles described in the Quran centuries before their modern discovery. Surah Al-Kahf is particularly significant in this context, as it directly addresses wormholes, space-time curvature, and gravitational effects. To fully comprehend this, firstly we must understand what “Al-Kahf” truly represents in the Quran. This study explores the scientific properties of Al-Kahf and its relation to relativity, gravitational lensing, and space-time warping. While modern science views Spacetime Curvature, wormholes and time dilation, as extraordinary phenomena, The Quran presents them as fundamental aspects of the universe, and are also utilized in divine operations. These principles are not isolated mentions but are woven throughout the Quran, highlighting the Quran’s deep engagement with the fabric of space-time. By integrating Quranic insights with General Relativity and modern astrophysics, this paper challenges conventional narratives of scientific history, advocating for a reassessment of the Quran’s contributions to humanity’s understanding of space-time and relativity. This interdisciplinary approach highlights that the Quran contains detailed direct descriptions of these cosmic phenomenon that align with cutting-edge physics, reinforcing the need for a historical reevaluation of scientific knowledge.